In vitro cloning of animal-infective bloodstream forms of Trypanosoma brucei - Hirumi, H.; Hirumi, K.; Doyle, J.J.; Cross, G.A.M. (Cambridge University Press, 1980)
Clones of animal-infective bloodstream forms of Trypanosoma brucei (stocks S.427 and LUMP 227) were made by transferring a single organism from bloodstream-form cultures into each well of Microtest II Tissue Culture Plates containing bovine fibroblast-like feeder cells. When the number of trypanosomes increased to 102–103/well on days 4–16, they were transferred into plastic T-25 culture flasks also containing feeder cells and fresh medium. Cultures were thereafter maintained by partially replacing the trypanosome suspension with the same volume of fresh medium (diluting the density to 2–5 × 105 trypanosomes/ml) every 24 h. Sub-cultivations could be made by transferring 1–2 ml of the trypanosome suspension to a new culture flask at 4–5 day intervals. A total of 42 clones in the 3 series TC221, TC52 and TC227, carrying variable antigen types (VATs) 221, 052 and ILTat 1·4, respectively, have been established. Average population doubling times for clones of TC221, TC52 and TC227 were 8·7, 14·5 and 15·5 h respectively. Of 35 populations examined, 34 clones retained the original specificity of their VATs for at least 8–32 days from cloning. One cloned population of TC52 consisted of 99·8% VAT 052 and 0·2% VAT 221 at the time when the first VAT test was made on day 18.